Development and assessment of a fast pyrolysis reactor for bio-oil, syngas and bio-char production from biomass residues - Razzaque, Md Abdur (2016)
Design, development and assessment of a Fluidized Bed Reactor (FBR) is a very complex process, where enormous empirical correlations; charts and graphs; lot of parameters, assumptions, unit operations are involved, straight forward design equations and design data are limited, and generally the operation of the system requires many adjustments. The improved design of FBR with high coefficient of performance (COP), low energy consumption, high yield and environmentally friendly (low emission) is the target. The scope of the study is to design and fabrication of a lab scale fluidized bed fast pyrolysis system with throughput capacity of 1 kg of dry biomass per hour which includes a bubbling fluidized bed reactor, 2 cyclone separators in series, 4 condensers in series operating between temperatures of 600-300; 300-200; 200-125 and 125-40 ̊C to selectively condense alkanes, phenols, aromatics, indene, methyl-indene, benzene, toluene, methyl–naphthalene, esters, acids, alcohols, ketones; 2 heaters (1 pre-and 1 primary), an auger feeder with hopper and controller, blowers and rig structure. A 3-D simulation was performed to facilitate the mounting of different unit operations, instruments and control panels with sufficient maintenance and manoeuvring accessibilities yet compact structure with low structural footprints.